Neutron Chareacterization of BNCT Water Phantom Based on 30 MeV Cyclotron Using PHITS Computational Code - Okti Dyah Rahayuningsih; Susilo Susilo; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2019)
Cancer is the second leading cause of death globally and was responsible for 8,8 million deaths in 2015. Approximately 70% of deaths from cancer occur in low- and middle-income countries. The war on cancer has been fought with three tools – surgery (cut), radiation therapy (burn) including radiotherapy and bracytherapy, and also chemotherapy (poison). Cancer therapy has increased life expectancy of patients but each treatment modality has its own effects, complications and toxicity. Moreover we have found a new effective method to fight cancer, that is, Boron Neutron Capture Therapy (BNCT). Boron Neutron Capture Therapy (BNCT) has for many decades been advocated as an innovative form of radiotherapy that, in principle, has the potential to be the ideal form of treatment for many types of cancers. This research’s aim is the characterising neutron of BNCT water phantom based on 30 MeV cyclotron using PHITS computational code. The result from the simulation is that thickness of the water phantom, related to flux neutron.